2020
DOI: 10.1097/mop.0000000000000894
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapies for infants and children in the ICU

Abstract: Purpose of review-Pediatric acute kidney injury (AKI) in critically ill patients is associated with increased morbidity and mortality. Emerging data support that the incidence of pediatric AKI in the ICU is rising. For children with severe AKI, renal replacement therapy (RRT) can provide a lifesaving supportive therapy. The optimal timing to deliver and modality by which to deliver RRT remain a point of discussion within pediatric (and adult) literature. This review discusses the use of RRT for pediatric patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 58 publications
1
26
0
4
Order By: Relevance
“… 1 Following a rapid increase in dialysis use over a period of approximately two decades, the incidence of dialysis initiation in most high-income countries reached a peak in the early 2000s and has remained stable or has decreased slightly since then. 2 However, mortality remains unacceptably high among patients on dialysis, especially in the first 3 months following initiation of HD treatment. According to the 2019 Annual Data Report from the U.S. Renal Data System, the annual mortality was 156 per 1000 patient-years for patients undergoing PD and 167 patients for those receiving HD in the United States.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Following a rapid increase in dialysis use over a period of approximately two decades, the incidence of dialysis initiation in most high-income countries reached a peak in the early 2000s and has remained stable or has decreased slightly since then. 2 However, mortality remains unacceptably high among patients on dialysis, especially in the first 3 months following initiation of HD treatment. According to the 2019 Annual Data Report from the U.S. Renal Data System, the annual mortality was 156 per 1000 patient-years for patients undergoing PD and 167 patients for those receiving HD in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous kidney replacement therapy has led to improvements in the outcomes of dialysis complications and is superior to intermittent hemodialysis in maintaining hemodynamic stability and preventing a re-increase of toxic metabolites [ 4 ]. Multiple CKRT techniques have been developed, all of which are safe and efficacious, and among which, CVVHD enables a higher toxic metabolite clearance rate than continuous venovenous hemofiltration (CVVH) for the management of hyperammonemia and hyperleucinemia [ 4 , 19 , 20 ]. In the present study, the CVVHD (57.1%) and CVVHDF (42.9%) modalities were analyzed, and the CVVHD modality was found to be used in most MSUD dialysis sessions (78.6%), as the rapid removal of leucine is not as important as ammonia removal.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all these advantages, providers need to be aware of the potential complications of CKRT, the most often reported of which are thrombocytopenia, hypotension, hypocalcemia, hypokalemia, hypothermia, complications of anticoagulation, complications due to vascular access such as bleeding, and thrombosis [ 20 ]. The disadvantages of CKRT relate primarily to technical difficulties, including complications in the insertion of catheters for neonates and infants, and low body-weight children.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25% of the children admitted to the ICU will develop acute kidney injury, and 4-6% will need RRT [145,146]. Currently, most ICUs apply RRT as continuous veno-venous hemofiltration with (CVVHDF) or without (CVVH) dialysis [146].…”
Section: Continuous Renal Replacement Therapymentioning
confidence: 99%
“…Approximately 25% of the children admitted to the ICU will develop acute kidney injury, and 4-6% will need RRT [145,146]. Currently, most ICUs apply RRT as continuous veno-venous hemofiltration with (CVVHDF) or without (CVVH) dialysis [146]. It has been suggested that continuous RRT (CRRT) may also contribute to additional antibiotic PK variability in critically ill patients.…”
Section: Continuous Renal Replacement Therapymentioning
confidence: 99%